Effects of Severe Plastic Deformation on the Mechanical Properties of Welded ST37-2 Steel - Sahhal, A.; Gunay, M. (Engineering, Technology & Applied Science Research, 2020)
Cold treatment techniques are used to enhance the mechanical properties of metal alloys, whose most important characteristics are strength, roughness, and microstructure. The aim of this research is to test the effect of Conventional Shot Peening (CSP) and Severe Shot Peening (SSP) on the mechanical properties of ST37-2 steel. The results of the experiments showed enhancements in surface roughness and tensile strength. However, shot peening decreased the ductility of the metal and caused changes in its microstructure that are indicated in the XRF and XRD tests. Results’ data are provided as an original contribution to the literature while they are compared with the existing data.